BUDIDAYA KELAPA DI PANTAI TIMUR JAMBI DALAM LINTAS SEJARAH - Maharani, Dyini (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
This scientific article contains about coconut cultivation in Jambi, especially the East Coast area of Jambi by the Banjar People. As is known that coconut has many benefits and is a large export commodity. With the cultivation of coconuts on the East Coast of Jambi, the Banjar people can produce their own coconuts and copra and export them to various regions outside Jambi. The writing of this article is presented qualitatively to obtain a descriptive picture of coconut cultivation by processing the results of interviews and related literature. The results of this study show that Banjar people are very familiar with the agrarian world, namely plantations and agriculture. The Kuala Jambi area is well managed to produce high quality coconuts. Coconut cultivation has a big impact on the economy of people living on the East Coast of Jambi, because coconut cultivation is very easy to do, supported by a good drainage system and a strategic cultivation location, which is crossed by trade routes, both land and sea routes.